Evaluation of Phenolic Content and Antioxidant Capacity of Eleusine coracana (L.) - Jignasu P. Mehta; Chirag R. Fultariya; Pravin H. Parmar; Solhil H. Vadia; Balubhai A. Golkiya (E-Journal of Chemistry)
The aim of this study is to evaluate the content of phenolics: total seven phenolic acids and one flavonoid were separated from the species of Eleusine coracana (L.). The separated phenolics were characterized by various spectral techniques. The antioxidant capacity of all phenolics was determined by rancimat study of sunflower oil using control and standard drugs like Glipizide and Metformin. The stability period of sunflower oil was found to increase from 0.89 hr to 1.04 hr in presence of eight extracted ingredients of Eleusine coracana (L.), which was compared with result of neat sunflower oil.